Optimization of FIB milling procedure for micromechanical testing of cement pastes - Jan Procházka; Jiří Němeček; Patricie Halodová; Jiří Němeček (Acta Polytechnica CTU Proceedings, 2024)
This study focuses on optimizing the Focused Ion Beam (FIB) preparation process for micro-beams made from cement paste prepared from Portland cement CEM I-42.5R, which includes four phases: inner and outer products, Portlandite, and residual clinker. The effects of the primary electron beam, focused ion beam, image drift, imaging issues, and sample moisture cycling were investigated. Recommendations on specific fabrication procedures and FIB milling parameters, such as accelerating voltage, probe current, and time, were provided.